Implementasi Kebijakan Pemerintah Daerah Terkait Program Unggulan di Kabupaten Luwu Utara - Wijaya, Sakral (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Regional government policy is a legal product because every village government has this authority. The purpose of this research is to find out the Implementation of Regional Government Policy Regarding Main Programs in North Luwu Regency and what are the supporting and inhibiting factors. The method used in this study was qualitative, using data collection techniques namely observation, interviews and documentation. Based on the results of field research, it was obtained that the Implementation of Regional government's policy Regarding Main Programs in North Luwu Regency was not optimal because it can be seen from several supporting and inhibiting aspects of inplementating this superior program. Then the facilities and infrastructure provided by the regional government are still far from the expectations of the community. In addition, there is also the factor of a lack of community involvement in building communication with the North Luwu District Government because the government builds sectoral communication and the community is also tend to be indifferent regarding local government policies.